TRADITIONAL BUILDING TECHNIQUES OF THE HELLENISTIC PERIOD IN THE KHABUR VALLEY, SYRIA: THE CASES OF TELL HALAF AND TELL BEYDAR - Cabral, Ricardo; Costa, Tiago; Katzy, Elisabeth; Lopes, Maria Conceição; Schmid, Jochen; Tomé, André; Vaz, Ana (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The present paper aims to provide an overview of the building materials and techniques employed by the communities that settled in Khabur Valley, Syria during the Hellenistic period. The research was conducted under the recently established collaboration between the Tell Beydar Archeological Project and Syro-German Excavations at Tell Halaf. It focuses on a region in the dry plains of Northern Mesopotamia that reveals how the local communities, facing scarce natural resources, were able to adapt to the strict environmental setting while relying exclusively on earthen architecture. Construction shows the use of both rammed-earth and adobe, either together in different parts of the same building, or independently and related to speciic functions. Finally, the analysis of the building techniques of this region could shed some light on the degree of interplay between the local and Hellenistic inluences.